2021
DOI: 10.1080/02646838.2021.1921716
|View full text |Cite
|
Sign up to set email alerts
|

Mother-infant bonding screening in a sample of postpartum women: comparison between online vs offline format

Abstract: Aims: The use of the internet to assess mother-infant bonding (MIB) has not been extensively examined. The main aim of this study was to compare offline (paper-and-pencil) and online MIB screening in a sample of n=1,269 women. We tested the reliability and factorial structure of the Postpartum Bonding Questionnaire (PBQ) and also compared clinical, obstetrical, reproductive, and psychopathological variables related to poor MIB. Methods: A cross-sectional study was conducted on 1,269 mothers. The offline group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Women recruited online reported more previous miscarriages than those in the face-to-face group. We hypothesize that this finding could be associated with the intimacy and sense of security that the online method offers to answer an uncomfortable question anonymously, as pointed out by other authors [ 40 ]. In this sense, online recruitment would show an advantage over the face-to-face recruitment of participants by ensuring anonymity.…”
Section: Discussionmentioning
confidence: 53%
“…Women recruited online reported more previous miscarriages than those in the face-to-face group. We hypothesize that this finding could be associated with the intimacy and sense of security that the online method offers to answer an uncomfortable question anonymously, as pointed out by other authors [ 40 ]. In this sense, online recruitment would show an advantage over the face-to-face recruitment of participants by ensuring anonymity.…”
Section: Discussionmentioning
confidence: 53%
“…This difference in assessments is a result of following up on a fairly large sample. Recent research of offline vs. online assessment of the PBQ found no difference between assessment modalities in terms of associations with sociodemographic, reproductive, obstetric, and psychological outcomes ( 61 ). Lastly, our participants were mostly Jewish, sampled from one health center only, and this may impair our ability to generalize our findings, as parenting practices may be different across cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies observed women's actions and behaviors in responding to PRMs questionnaires in routine maternity care, including participation, response, completion, and compliance to follow-up support or care 20,24,[26][27][28][29][30][31][32][33][34][36][37][38][39][40]44 (see Table 2).…”
Section: User's Action and Behaviormentioning
confidence: 99%
“…According to eight studies 26,30,[32][33][34]36,37,39 26 Kim et al, 30 Kingston et al, 32 La Porte et al, 33 Lasheras et al, 34 Lawson et al, 36 Marcano-Belisario et al, 37 Matthey et al 39 Average of participation rates: 85.01% (considering sample size of each study) Range of participation rates: 67.00%-98.50% Participation (average) in different geographical areas: Europe, 93.07%; Australia, 80.00%; North America, 76.43%; Others, Japan and Kenya, no relevant data Participation (average) for different data collection tools and platforms: Paper, 98.42%; web, 94.69%; app, 84.06%; SMS or automated voice messaging, 67.78% Other key points • The main reasons of women's refusal to participate included a lack of interest, a lack of time, technical barriers and worry about missing appointments while answering PRMs questions during waiting time at clinic sites (Kim et al, 30 La Porte et al, 33 Marcano-Belisario et al 37 )…”
Section: User's Action and Behaviormentioning
confidence: 99%
See 1 more Smart Citation